From Bedside to Board: Lived Transitions of Novice Nursing Administrators with Postgraduate Degrees in China - Li, Xiaoxi; Espinosa, Perry Paul; Trajera, Sheilla M.; Ching, Gregory S. (International Journal of Basic and Applied Sciences, 2025)
Hospitals increasingly promote clinically expert, postgraduate-prepared nurses into first-line administration, yet the transition from bedside to leadership is often under-supported. This descriptive phenomenological study explored early career growth among ten novice nursing administrators (nine head nurses, one nursing-quality officer) in a tertiary public hospital in Henan Province, China. Semi-structured interviews (32-70 minutes) were analyzed with Colaizzi’s method in NVivo 12. Trustworthiness was strengthened through member checking, peer debriefing, external audit, triangulation of field notes and reflexive journals, and thick description. Four themes emerged: (1) Challenges encountered in nursing management process; complicated in administration (competing role demands), challenges in innovation, challenges in communication and coordination, and lack of administration and professional experience; (2) Growth in nursing administration process; cognitive transformation in nursing profession, improvement of administration ability, and developing psychological quality (resilience); (3) Advisement for other novice nursing administrators; prepare for role transition, advance professional competence (build technical credibility), seek support actively (mentorship and networks), and investing in higher education (appropriately leverage postgraduate education); and (4) Suggestions for nurses with postgraduate degrees; clarify future career direction, maintain original intentions, avoid assimilation, be willing to dedicate and integrate into the team, and develop versatility, pursue continuous learning. A “mountain-journey” simulacrum integrates Self-Leadership Theory, Benner’s Novice-to-Expert model, and McClelland’s Human Motivation Theory to depict progression from instability to a consolidated leadership identity. Postgraduate preparation confers advantages, but does not substitute for structured transition support; institutions should formalize mentorship, implement competency-based orientation, and align incentives with innovation and evidence-based practice to accelerate safe, confident leadership among novice nurse administrators.